1994
DOI: 10.2186/jjps.38.966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Measuring System for Occlusal Force with Pressure Sensitive Sheet.

Abstract: : An occlusal diagnostic system was evaluated for clinical applications.This system consists of pressure sensitive sheets (DENTAL PRESCALE (R), Fuji Photo Film Co.) and the analyzing computer (OCCLUZER FPD 703 (R), Fuji Photo Film Co.). Effects of velocity and duration of pressure and temperature upon color forming of pressure sensitive sheets were examined. While simulating intraoral applications, the accuracy of this system was examined using maxillary and mandibular casts.The results were as follows:1. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The system is not affected by intraoral temperature or humidity, nor is it affected by the velocity or duration of pressure. 19 Moreover, its performance is not dependent on the proficiency of the examiner, and it is simple to use for objective evaluation of occlusal function. 12 In a previous study, occlusal contact area and force were reported to be greater in male patients than in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…The system is not affected by intraoral temperature or humidity, nor is it affected by the velocity or duration of pressure. 19 Moreover, its performance is not dependent on the proficiency of the examiner, and it is simple to use for objective evaluation of occlusal function. 12 In a previous study, occlusal contact area and force were reported to be greater in male patients than in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…The sheet is unaffected by temperature change, 22 and the velocity and duration of the force applied to it have a negligible influence. 23 For all study models, the upper and lower side cuts, heel cuts, and baselines were exactly on the same plane in centric occlusion. For OCA measurements, the casts were mounted in a centric occlusion adjustable articulator.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that OcFr in maximum intercuspation can be recorded repeatedly with little error using a similar methodology (Matsui et al ., 1996; Hassan et al ., 1997). The film is unaffected by intraoral humidity and temperature (Noguchi et al ., 1983) and the velocity and duration of the forces applied to it have negligible influences on colour formation (Suzuki et al ., 1994).…”
Section: Methodsmentioning
confidence: 99%